2020
DOI: 10.1038/s41597-020-00587-y
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution monthly precipitation and temperature time series from 2006 to 2100

Abstract: the CHELSA algorithm 17 , which provides a more accurate representation of temperature and precipitation in highly complex terrain. Data based on the CHELSA algorithm 17 have already been used to infer e.g. ecological niches 24 , soil nutrients 25,26 , or to assess climate change impacts of forests 27 , insect pests 28 , and biodiversity 29. Mean monthly maximum daily temperatures and mean monthly minimum daily temperatures have been downscaled using the delta change method based on the high-spatial-resolution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 70 publications
(82 reference statements)
0
95
0
1
Order By: Relevance
“…From these downscaled CHELSA 1.2 time series, we derived four climate variables to retrace past conditions during the establishment of today's adult trees: yearly mean temperature and precipitation sum, and mean temperature and summed precipitation over the growing season (May–October). For future data, we used the CHELSA cmip5 ts (available for RCP4.5 and RCP8.5; Karger et al, 2020) based on the five most informative models (Sanderson et al, 2015) in the Alps for the reference period 2061–2080. Projected future climate variables were taken from five global circulation models (GCMs), which were downscaled to 1 km × 1 km resolution using an additive (for temperature), or multiplicative (for precipitation) change factor method using CHELSA 1.2 as a baseline.…”
Section: Methodsmentioning
confidence: 99%
“…From these downscaled CHELSA 1.2 time series, we derived four climate variables to retrace past conditions during the establishment of today's adult trees: yearly mean temperature and precipitation sum, and mean temperature and summed precipitation over the growing season (May–October). For future data, we used the CHELSA cmip5 ts (available for RCP4.5 and RCP8.5; Karger et al, 2020) based on the five most informative models (Sanderson et al, 2015) in the Alps for the reference period 2061–2080. Projected future climate variables were taken from five global circulation models (GCMs), which were downscaled to 1 km × 1 km resolution using an additive (for temperature), or multiplicative (for precipitation) change factor method using CHELSA 1.2 as a baseline.…”
Section: Methodsmentioning
confidence: 99%
“…resolution in a World Mercator projection. Orographic precipitation effects are less pronounced just above the surface, as well as in the free atmosphere above the planetary boundary layer (Daly et al, 1997;Karger et al, 2020;Oke, 2002;Stull, 2012). The highest impact of orography is considered just at the boundary layer height where the airflow interacts with the terrain.…”
Section: Precipitation Estimationmentioning
confidence: 99%
“…For the recent past the gap between the coarse GCM resolution and the high resolution needed has be bridged using satellite data (Biasutti et al, 2011;Funk et al, 2015;Huffman et al, 2007), statistical downscaling (Karger et al, 2017a(Karger et al, , 2020Maraun et al, 2010;Schmidli et al, 2006;Wilby et al, 1998;Wood et al, 2004), dynamical downscaling (Skamarock et al, 2019), or interpolation of meteorological station data (Daly et al, 1997;Harris et al, 2020;Hijmans et al, 2005;Meyer-Christoffer et al, 2015). While all of these methods work comparably well for current climatic conditions, satellite or station data are not available before the 19 th Century (end of the 20 th century for satellite data), hampering an application of said methods to paleoclimatic models.…”
Section: Introductionmentioning
confidence: 99%
“…S4a). The growing CO 2 concentrations can either increase AGB through enhanced photosynthetic rates (Fay et al, 2012;Lee et al, 2010) or have limited influences because of other environmental constraints on plant growth (Brookshire and Weaver, 2015). In this study, we deduced future AGB dynamics both including and not including the effect of CO 2 enrichment on grassland AGB.…”
Section: Regional Mapping and Uncertainty Analysismentioning
confidence: 99%
“…Furthermore, it has been reported that carbon dioxide (CO 2 ) enrichment may increase plant productivity through enhancing photosynthetic rates and reducing stomatal conductance, thereby increasing water use efficiency (Fay et al, 2012;Pastore et al, 2019). This might provide an opportunity to mitigate or even reverse the harmful effects of other environmental changes on grassland AGB (Lee et al, 2010), e.g. the enhanced water limitations resulting from climate warming.…”
Section: Introductionmentioning
confidence: 99%